2020
DOI: 10.21037/tcr-20-2192
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of the clinical significance of folate receptor- positive circulating tumor cell in the management of hepatobiliary- pancreatic cancers

Abstract: Background: Hepatobiliary-pancreatic cancers (HBPs) are highly lethal, partly because of their usually late diagnosis. This multi-center, observational study aimed to explore the clinical significance of folate receptor-positive circulating tumor cell (FR+CTC) as a liquid biopsy approach in the differential diagnosis and management of HBPs.Methods: We recruited 119 patients suspicious for HBPs and 60 cancer-free healthy individuals in the present study. Patients without definitive pathological assessment or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…28,29,[47][48][49] A few studies revealed that pre-and post-operative FR + CTC levels are strong risk factors of recurrence and prognosis and may be used for clinical decision making. [50][51][52][53] In stage IV NSCLC patients receiving first-line chemotherapy or targeted therapy, FR + CTC levels before and after treatment and the dynamic changes of FR + CTC during treatment were associated with progression-free survival. Similar results were found for SCLC patients with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29,[47][48][49] A few studies revealed that pre-and post-operative FR + CTC levels are strong risk factors of recurrence and prognosis and may be used for clinical decision making. [50][51][52][53] In stage IV NSCLC patients receiving first-line chemotherapy or targeted therapy, FR + CTC levels before and after treatment and the dynamic changes of FR + CTC during treatment were associated with progression-free survival. Similar results were found for SCLC patients with chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, FR has been adopted as a target for CTC enumeration and its applications in clinical diagnosis and prognosis in lung cancer have received much attention 28,29,47–49 . A few studies revealed that pre‐ and post‐operative FR + CTC levels are strong risk factors of recurrence and prognosis and may be used for clinical decision making 50–53 . In stage IV NSCLC patients receiving first‐line chemotherapy or targeted therapy, FR + CTC levels before and after treatment and the dynamic changes of FR + CTC during treatment were associated with progression‐free survival.…”
Section: Discussionmentioning
confidence: 99%